2019
DOI: 10.3390/w11040642
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Depletion Affects Kinematics and Shoaling Cohesion of Cyprinid Fish

Abstract: Numerous anthropogenic stressors impact rivers worldwide. Hypoxia, resulting from organic waste releases and eutrophication, occurs very commonly in Mediterranean rivers. Nonetheless, little is known about the effects of deoxygenation on the behavior of Mediterranean freshwater fish. To fill this knowledge gap, we assessed the impact of three different dissolved oxygen levels (normoxia, 48.4%, 16.5% saturation) on kinematics indicators (swimming velocity, acceleration, distance traveled) and shoaling cohesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The effects of deforestation, intensification of agriculture and other land-use changes, hydropower, river engineering, and water pollution threaten aquatic biodiversity (e.g. Clausen & York, 2008;Fitzgerald et al, 2018;Hayes et al, 2018Hayes et al, , 2019Meulenbroek et al, 2019). These trends can even have visible impacts on largescale ecosystem processes (Darwall et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of deforestation, intensification of agriculture and other land-use changes, hydropower, river engineering, and water pollution threaten aquatic biodiversity (e.g. Clausen & York, 2008;Fitzgerald et al, 2018;Hayes et al, 2018Hayes et al, , 2019Meulenbroek et al, 2019). These trends can even have visible impacts on largescale ecosystem processes (Darwall et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the wild, fish might try to escape from unfavorable conditions (Hayes et al, 2019). Barbel and some fish species usually reduce their swimming activity and adopt a "sit and wait" strategy (Domenici et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…A study showed that oxygen depletion levels affected the behavior and ecological responses of Luciobarbus bocagei (Hayes et al, 2019). Studies related to oxygen consumption in barred loach reported Stress responses of three species of cyprinid: common carp ..... (Wahyulia Cahyanti) that oxygen consumption under hypoxic conditions decreased significantly compared to normoxic conditions marked by decreased swimming activities (Iswantari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The term “hypoxic” is context-specific and can either refer to the level at which an organism responds to low oxygen conditions or to the environment in which the organism resides. For the purpose of this study, we characterize DO concentrations of 4.5 mg O 2 L −1 as Mild hypoxia 25 , 26 , 2.5 mg O 2 L −1 as Moderate hypoxia, and 1 mg O 2 L −1 as Severe hypoxia. Our previous studies indicate that previous exposure to the Moderate hypoxia increases H. carunculata ’s metabolic rate in the long-term 27 .…”
Section: Introductionmentioning
confidence: 99%
“…However, based on climate change models, chronic hypoxic events are more likely in the future 1 3 , 57 . In addition, due to unique physiological and behavioral responses at different levels of hypoxia 25 , 26 , gene expression associated with chronic Mild and Moderate DO should be investigated to understand organismal response. While it has been suggested that amphinomids may thrive in lowered DO conditions 58 60 , no studies have yet determined direct gene expression responses to this stressor.…”
Section: Introductionmentioning
confidence: 99%